b - 9; 9; 9; 9; 9; 9; 9; 9 (b, 2022)
Collection of memoirs on Murari Chand College, Bangladesh, by its alumni.
AAL
Keywords: Murari Chand College -- Alumni and alumnae; Universities and colleges -- Alumni and alumnae -- Bangladesh; Universities and colleges -- Bangladesh -- Sylhet District (Bangladesh) -- Congresses; Students -- Bangladesh -- Sylhet District (Bangladesh).; Universities and colleges -- Bangladesh -- Sylhet -- History